Globalization, structural transformation, and the labor income share - Ken Suzuki; Yoko Oishi; Saumik Paul (Asian Development Bank Institute (ADBI), 2018)
This paper provides novel empirical evidence on the role of trade and structural transformation as potential drivers of the labor income share. Using cross-country data, both at the national and sectoral level, we find that trade openness is negatively correlated with the labor income share. The findings are robust across national and disaggregated levels, and across different model specifications. However, the relationship between the process of structural transformation and labor income share is at best mixed. We also find weak evidence that skill-biased structural transformation is likely to be positively correlated with the share of labor income predominantly in the services sectors.
Keywords: E24; E25; N10; O14; 330; labor income share; structural transformation; globalization